Slowing gait during turning: how volition of modifying walking speed affects the gait pattern in healthy adults - Madrid, Julian; Benning, Leo; Selig, Mischa; Ulrich, Baptiste; Jolles, Brigitte M.; Favre, Julien; Benninger, David H. (Frontiers in Human Neuroscience, 2024)
• Volitionally reducing walking speed decreases cadence for all turning amplitudes in young adults • Volitionally reducing walking speed while turning decreases spatial parameters in young adults • Volitionally reducing walking speed while turning increases temporal parameters in young adults • Volitionally reducing walking speed while turning decreases spatial parameter's variability and increases temporal parameter's variability in young adults • Cadence might be a pace gait constant which is volitionally controlled to regulate the walking speed